Comparison of Client Centered and Behavioristic Approaches in Counseling - Dwiky Fajri Al-Ghiffari; Aprilia Sari Yudha2 (Journal of Science and Research, 2025)
An in-depth study of the comparison of Client-Centered and Behavioristic approaches to counseling has important significance in the development of effective counseling practices. The aims of this research are (1) to know the concept of client centered approach. (2) to know the concept of a behavioristic approach. (3) to know the comparison of client centered and behavioristic approaches. Literature research is carried out by collecting information through the literature, then recording and processing the data that has been obtained. The results of this study are (1) the client centered approach is an approach that empowers clients to think for themselves, solve their own problems, and achieve self-actualization. (2) The behavioristic approach in counseling is an approach that emphasizes changes in client behavior through the use of techniques based on learning principles. (3) The client-centered approach encourages counselors to create an environment that supports client exploration and problem solving, while the behavioristic approach involves identifying unwanted or maladaptive behaviors, as well as using structured techniques and strategies to reinforce desirable behaviors and change unwanted behaviors.